2023
DOI: 10.3390/electronics12092039
|View full text |Cite
|
Sign up to set email alerts
|

Financial Time Series Forecasting: A Data Stream Mining-Based System

Abstract: Data stream mining (DSM) represents a promising process to forecast financial time series exchange rate. Financial historical data generate several types of cyclical patterns that evolve, grow, decrease, and end up dying. Within historical data, we can notice long-term, seasonal, and irregular trends. All these changes make traditional static machine learning models not relevant to those study cases. The statistically unstable evolution of financial market behavior yields a progressive deterioration in any tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…For forecasting financial time series, Bousbaa et al [30] established data stream mining approaches. They used FOREX historical financial data to predict future values using a Particle Swarm Optimization (PSO) approach.…”
Section: Review Of Related Workmentioning
confidence: 99%
“…For forecasting financial time series, Bousbaa et al [30] established data stream mining approaches. They used FOREX historical financial data to predict future values using a Particle Swarm Optimization (PSO) approach.…”
Section: Review Of Related Workmentioning
confidence: 99%
“…Experimental results showed that CEEMD-MultiRocket ranked second in classification accuracy on the 109 datasets from the UCR repository against a spread of state-of-the-art TSC models, only behind HIVE-COTE 2.0, but with only 1.4% of the latter's computing load. Bousbaa et al [4] proposed an incremental and adaptive strategy using the online stochastic gradient descent algorithm (SGD) and particle swarm optimization metaheuristic (PSO). Two techniques were involved in data stream mining (DSM): adaptive sliding windows and change detection.…”
Section: Time Series Analysismentioning
confidence: 99%
“…The use of ANN algorithms in economic forecasting deviates from traditional methodologies, providing a datadriven methodology capable of adjusting to the complexities and uncertainties of real-world economic systems [5]. ANNs can use the large amounts of historical data available to make forecasts that account for the dynamic character of economic variables [6]. Furthermore, the intrinsic flexibility of ANN topologies enables the incorporation of a wide range of data sources, including macroeconomic variables, financial market data, and sociopolitical elements, thereby increasing the depth and accuracy of forecasting [7].…”
Section: Introductionmentioning
confidence: 99%